Variability in residual feed intake, nutrient utilisation and blood parametersin Murrah buffalo calves fed on total mixed ration - EBAID, ELSADIG IDRIS EISSA; DATT, CHANDER; SHARMA, VIJAY KUMAR; DUDI, KULDEEP; LATHWAL, SURINDER SINGH (The Indian Journal of Animal Sciences, 2024)
The present study was conducted on 18 female Murrah buffalo calves divided into two treatment groups to determine the residual feed intake, nutrient digestibility and blood metabolite parameters when fed with ration containing wheat (Triticum aestivum) straw, berseem (Trifolium alexandrinum) fodder as roughages and concentrate mixture to meet their requirements. Regular recording of body weight and feed intake was done during 90-day trial period. Residual feed intake (RFI) values were determined for individual animals based on which they were divided into low and high RFI groups. DM intake was lower in low RFI animals than high RFI animals. The blood glucose level and growth hormone level in low and high RFI group was comparable in both groups. Low RFI group had greater concentration of creatinine (1.62 vs. 1.21 mg/dL) as well as IGF-1 (136.70 vs. 120.38 ng/mL) whereas, concentration of total plasma protein level (6.80 vs 7.43 g/dL), albumin (3.46 vs 3.71 g/dl), aspartate aminotransferase (102.20 vs. 122.60 IU/L) and cortisol (3.48 vs. 5.32 ng/mL) were lesser in low RFI group with respect to high RFI group, indicating a positive correlation of RFI with total plasma protein, albumin, aspartate aminotransferase and cortisol and a negative correlation with plasma creatinine and IGF-1 levels in female Murrah buffalo calves. It was concluded that low RFI group of female Murrah buffalo calves showed better performance when fed with total mixed ration.